The factors of the low iodine concentration in soil cover and drinking waters of the second ridge of the Mountain Crimea - Victor Yu. Berezkin; Victor V. Glebov; Elena P. Kayukova (RUDN Journal of Ecology and Life Safety, 2023)
Low iodine content in the environment can be one of the main factors of iodine deficiency diseases in humans and farm animals, including hypothyroidism, nodular thyroid tumors, irreversible brain damage in the fetus and newborn. Endemic goiter, caused primarily by iodine deficiency, is an urgent problem for most regions of modern Russia, including the Republic of Crimea. For the Republic of Crimea, along with other regions of the Crimean-Caucasian mountain zone, there is a deficiency of iodine in the lower links of the trophic chain, which provokes iodine deficiency diseases. The aim of the work was to reveal the contrast of iodine distribution in the lower links of the trophic chain: different types of soils for agricultural use and natural waters for drinking purposes from various sources in the Crimean Mountains. The article presents data of the iodine content in the soil cover and drinking water in the Crimean Mountains, on the example of the Bakhchisarai area (in Bodrak river valley). The dependence of the iodine content in the upper horizons of different types of soils, on the content of humus, pH-water soils and cation exchange has been established. It has been confirmed that the content of iodine in natural waters (springs, rivers, lakes) is determined primarily by the composition of water-bearing rocks.